A Small GTPase RHO2 Plays an Important Role in Pre-infection Development in the Rice Blast Pathogen Magnaporthe oryzae - Fu, Teng; Kim, Joon-Oh; Han, Joon-Hee; Gumilang, Adiyantara; Lee, Yong-Hwan; Kim, Kyoung Su (The Plant Pathology Journal, 2018)
The rice blast pathogen is a global threat to rice production. Here we characterized gene ( ) that belongs to the Rho GTPase family, using a deletion mutant. This mutant exhibited no defects in conidiation and germination but developed only 6% of appressoria in response to a hydrophobic surface when compared to the wild-type progenitor. This result indicates that plays a role in appressorium development. Furthermore, exogenous cAMP treatment on the mutant led to appressoria that exhibited abnormal morphology on both hydrophobic and hydrophilic surfaces. These outcomes suggested the involvement of in cAMP-mediated appressorium development. mutation also delayed the development of appressorium-like structures (ALS) at hyphal tips on hydrophobic surface, which were also abnormally shaped. These results suggested that is involved in morphological development of appressoria and ALS from conidia and hyphae, respectively. As expected, mutant was defective in plant penetration, but was still able to cause lesions, albeit at a reduced rate on wounded plants. These results implied that plays a role in virulence as well.